2023
DOI: 10.1101/2023.02.10.528062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory innervation of masseter, temporal and lateral pterygoid muscles in common marmosets

Abstract: Myogenous temporomandibular disorders (TMD-M) are the most prevalent group of painful orofacial conditions, and the second most frequent among musculoskeletal pain conditions. TMD-M is associated with an increased responsiveness of nerves innervating the masseter (MM), temporal (TM), medial pterygoid closing (MPM) and lateral pterygoid gliding muscles (LPM). Treatment of this disorder remains difficult and is further complicated by each muscle having diverse and functionally distinct nerve innervation. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 76 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported that a single trigeminal ganglion cell innervates multiple regions. For example, single cells are known to project to both the nasal epithelium and olfactory bulb (Schaefer et al., 2002), to multiple masticatory muscles and temporomandibular joint (Hovhannisyan et al., 2023), and to both the tongue and pulp of a mandibular molar (Ohara et al., 2013). In the last experiment of the current study, double fluorescent labeling was performed by injecting AAV PHP.S‐CAG‐tdTomato in combination with fast blue, but no double‐labeled ganglion cells were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that a single trigeminal ganglion cell innervates multiple regions. For example, single cells are known to project to both the nasal epithelium and olfactory bulb (Schaefer et al., 2002), to multiple masticatory muscles and temporomandibular joint (Hovhannisyan et al., 2023), and to both the tongue and pulp of a mandibular molar (Ohara et al., 2013). In the last experiment of the current study, double fluorescent labeling was performed by injecting AAV PHP.S‐CAG‐tdTomato in combination with fast blue, but no double‐labeled ganglion cells were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The greater distribution of small thermosensitive ganglion neurons in the skin/mucosa, rather than in deep tissues, may be important for protection against burns from hot and cold temperatures in the external environment. Recently, it has been reported that not only differences in cell body size but also the expression patterns of chemical markers are characteristics in ganglion cells innervating different regions (Ambalavanar et al., 2003; Buchholtz et al., 2020; Hovhannisyan et al., 2023; Ibrahim et al., 2023; Leijon et al., 2019; Lindquist et al., 2021; Reid et al., 2011; Wu et al., 2018; Yang et al., 2022). In the future, the integration of data on chemical markers expressed by ganglion cells, axonal projection targets, and cell body localization within the trigeminal ganglion should provide a complete picture of trigeminal ganglion function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation